Role of bone marrow infiltration in management of delayed union of long bones fracture - Meena, Sanjay Kumar; Goyal, Naveen; Tetarwal, Devendra; Sharma, Bharat (International Journal of Research in Orthopaedics, 2020)
Background: Usually delayed union of fracture long bones are managed by putting a bone graft at fracture site , but bone grafting have donor site complication like scar, infection ,hernia ,gait disturbance , cosmetic problem, as well as recipient site complication like soft tissue trauma , de-vascularisation of fracture fragment. Bone marrow infiltration is a minimally invasive method done percutaneously. It is easy, safe procedure with no associated complications that may occur in bone grafting. Methods: This prospective study was conducted in the Department of orthopedics, Government Medical College, Kota from June 2011 to November 2013 to evaluate the efficacy of percutaneous bone marrow infiltration in cases of delayed union of long bones. 27 patients included in study with 28 bones, as one patient has given bone marrow injection in two bones (tibia & femur), so the cases included in study counted as 28 cases. The mean age of this study was 38.28 years, ranging from 18 years to 75 years. All cases were follow up after 4 to 6 weeks and thereafter one month interval. Final follow up was taken when fracture site shows clinical and radiological sign of union. Results: Out of 23 united cases 19 had excellent results and 04 cases had good results. The five cases which fail to unite were taken as poor results. Conclusions: Bone marrow infiltration is a minimally invasive, safe bone graft substitute for delayed union of long bones and have less complications.